Ways to Be Understood: The Ontological Turn and Interpretive Social Science. - Sivado, Akos (Philosophy of the Social Sciences, 2020)
The ontological turn in anthropological methodology, at least in its conceptualization-oriented formulation, aims to turn away from the concepts and objects found within one's own social setting in order to turn to indigenous conceptualization processes and take a look at "the things (and persons) themselves." This article aims to unpack what such constant reconceptualization amounts to, arguing that when modified to meet certain objections, the ontological turn could provide important ingredients for an alternative version of interpretive social science—one that wishes to understand social phenomena as human kinds in the vein of Ian Hacking, Sally Haslanger and Ron Mallon.